2023
DOI: 10.3390/jcm12103507
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Bypass Surgery versus Endovascular Revascularization in Long Femoropopliteal Lesions

Abstract: Long-term follow-up data comparing surgical and endovascular revascularization of femoropopliteal lesions is rarely reported. This study presents 4-year results of revascularization for long femoropopliteal lesions (Trans-Atlantic Inter-Society Consensus Types C and D) with vein bypass (VBP), polytetrafluorethylene bypass (PTFE), and endovascular intervention with a nitinol stent (NS). Data from a randomized-controlled trial on VBP and NS was compared with a retrospective patient cohort using PTFE with the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(26 reference statements)
1
0
0
Order By: Relevance
“…Other authors have reported significantly lower patency rates for bare nitinol stents. Primary patency at 3 years was 32%, primary-assisted 43%, and secondary patency 53% [20]. ZILVERPASS, Viabahn, and our study results indicate remarkably higher patency rates.…”
Section: Discussionsupporting
confidence: 50%
“…Other authors have reported significantly lower patency rates for bare nitinol stents. Primary patency at 3 years was 32%, primary-assisted 43%, and secondary patency 53% [20]. ZILVERPASS, Viabahn, and our study results indicate remarkably higher patency rates.…”
Section: Discussionsupporting
confidence: 50%